Mechanical behaviours of concrete segmented tunnel considering the effects of grouting voids — A 3D numerical simulation - Xiaohua Bao; Xianlong Wu; Xuehui Zhang; Jun Shen; Xiangsheng Chen; Pengliang Dang; Hongzhi Cui (Case Studies in Construction Materials)
Concrete segments are commonly utilized as linings in shield tunnels to support the load from the surrounding ground, with their mechanical performance playing a crucial role in ensuring tunnel safety. During the construction of shield tunnels, these segments are assembled on-site, and grouting is performed concurrently to promptly fill the gap between the segment and the surrounding ground. However, inadequate grouting can lead to the formation of voids, which are hidden construction defects that compromise the mechanical stability of the tunnel segments. This study explores the impact of grouting voids on the mechanical performance of concrete segmental tunnels during construction using a 3D numerical simulation. A 3D finite-element model of a segmented shield tunnel with grouting voids was developed based on the load-structure method. The analysis focused on the effects of void characteristics, such as their angle, position, and length, on the tunnel's mechanical behavior. The results indicate that voids located at the tunnel crown reduce the vertical convergence of the tunnel cross-section, while voids at the waist exacerbate its horizontal convergence. Additionally, the presence of voids alters the bending moment distribution in the segments. Compared to the case without a void, there is a reversal of the bending moment when the void is located at the crown, and the bending moment increases from −13 kN·m to 24 kN·m, potentially causing tensile damage. Furthermore, voids also induce stress concentration within the segments, and the maximum stress concentration factor (SCF) occurs at the center of the voids as 2.44. However, when a circumferential joint intersects the void, joint opening causes stress redistribution, with the most significant stress concentration appearing at 45° on both sides of the void. These findings contribute to better damage recognition and enhance the safety assurance of concrete shield tunnels.